If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3n + -1) = (4n + 7) + 3 Reorder the terms: 6(-1 + 3n) = (4n + 7) + 3 (-1 * 6 + 3n * 6) = (4n + 7) + 3 (-6 + 18n) = (4n + 7) + 3 Reorder the terms: -6 + 18n = (7 + 4n) + 3 Remove parenthesis around (7 + 4n) -6 + 18n = 7 + 4n + 3 Reorder the terms: -6 + 18n = 7 + 3 + 4n Combine like terms: 7 + 3 = 10 -6 + 18n = 10 + 4n Solving -6 + 18n = 10 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. -6 + 18n + -4n = 10 + 4n + -4n Combine like terms: 18n + -4n = 14n -6 + 14n = 10 + 4n + -4n Combine like terms: 4n + -4n = 0 -6 + 14n = 10 + 0 -6 + 14n = 10 Add '6' to each side of the equation. -6 + 6 + 14n = 10 + 6 Combine like terms: -6 + 6 = 0 0 + 14n = 10 + 6 14n = 10 + 6 Combine like terms: 10 + 6 = 16 14n = 16 Divide each side by '14'. n = 1.142857143 Simplifying n = 1.142857143
| 312.50=a+0.25a | | (9x+21)+(11x-1)=180 | | -4(t-2)+7t=5t-5 | | (6x+8)+(8x-6)=180 | | (y+x)dy-(y-x)dx=0 | | -8(x+1)+4(3x-7)=3(x-4)+10 | | 2(8x+48)=80 | | 0.18(y-4)+0.20y=0.14y-0.01(60) | | 3(k-5)=-45 | | 8(x+1)+5=2x+6(2+x) | | 8-4r=0 | | 9-4r=0 | | 6(x+6)=12x-12 | | 5m^2-11m-7=5 | | 4wx+wz-3yz-12xy=0 | | 6u^3+16u^2+8u=0 | | 7x=6y+18 | | 3x+18+33y= | | 24x+24=12x-12 | | 8k-5=18 | | -18p-6(4-4p)=2(p-2)-4 | | 4(-3x+1)-3x=-11 | | 12x+12=9x-9 | | 3x+1=32x+8 | | 4z=z | | 10x^3-2x^2+152=0 | | (48x-48)=(27+162) | | x+5x+2x+12+27+3=180 | | Y=(4x)(4x^3) | | 3(x+5)=2 | | 18=17+5m | | 5y-8=30 |